Massive Central Pulmonary Embolism with Riding Embolus and Concomitant Aortic Arch Embolism—Should We Diagnose Patients Earlier for Blood Clotting Disorders? Case Report - Anna Lis; Paweł Kowalski; Marcin Wita; Tomasz Zawadzki; Tomasz Ilczak; Wojciech Żurawiński; Mateusz Majewski (Journal of Cardiovascular Development and Disease)
Paradoxical embolism occurs when a clot originates in the venous system and traverses through a pulmonary or intracardiac shunt into the systemic circulation, with a mortality rate of around 18%. The risk factors for arterial embolism and venous thrombosis are similar, but different disease entities can lead to a hypercoagulable state of the blood, including antithrombin III (AT III) deficiency. We report the case of a 43-year-old man with a massive central pulmonary embolism with a rider embolus and concomitant aortic arch embolism with involvement of the brachiocephalic trunk, bilateral subclavian and axillary arteries, and the right vertebral artery, followed by a secondary ischaemic stroke. The Pulmonary Embolism Response Team (PERT) consulted the patient on several occasions; he was treated initially with an intravenous infusion of unfractionated heparin under activation partial thromboplastin time (APTT) and AT III substitution. After several days of hospitalisation and the conversion of pharmacotherapy to oral anticoagulants, the patient was discharged home in a stable condition with recommendations for further follow-up in appropriate clinics. This case highlights the role of in-depth diagnostics for coagulation disorders in patients after pulmonary embolism, especially without known risk factors.